Medialny obraz transplantacji ex mortuo a przepisy prawa - Olejniczak, Elwira; Kukieła, Beata (Acta Universitatis Lodziensis. Folia Linguistica, 2012)
Mass media play a very important role in shaping public opinion about organ transplantation. This article presents the characteristics of an ex mortuo transplantation image, in comparison with legal rights. The language, as well as social, ethical, religious and legal aspects are described. The authors draw a conclusion that the differences in understanding ex mortuo transplantations between Polish people and law are significant.